Condensation of capillary water and decreased surface energy cause increased soil water repellency in sandy soil. (15th December 2022) - Wong, Enoch V. S.; Ward, Philip R.; Leopold, Matthias; Murphy, Daniel V.; Barton, Louise
Abstract: Predicting soil water availability to crops in water‐repellent sandy soil is complicated as soil water repellency (SWR) responds non‐linearly to soil water content. Others have hypothesised that the development of a monolayer of water molecules results in SWR increasing before SWR declines with a further increase in soil water content. In a previous study, we found that SWR increases when above 0.28–0.86% threshold soil water content. Thus, our objective was to determine the underlying mechanisms responsible for why SWR increases when above a certain threshold soil water content in a sandy soil. A water adsorption isotherm was constructed by exposing a water‐repellent sandy soil to increasing relative humidity (dynamic vapour sorption technique) to evaluate if the development of a monolayer of water molecules was responsible for the increased SWR response. The increased SWR when above 0.66% threshold soil water content was found to coincide with the capillary condensation of water in the soil. The inverse gas chromatography technique was used for the first time in soil particles' surface energy analysis to investigate why SWR increases when above the threshold soil water content by determining the total, dispersive (non‐polar), and specific surface (polar) energy of the soil at two relative humidities (0% and 90%). Wettable sandy soil (98% soil organic carbon removed) was included as a control to further assess if soil organic carbon in the water‐repellent soil influences the surface energy of the soil. The mean of total, dispersive, and specific surface energy decreased for both wettable and water‐repellent sandy soils when exposed to 90% relative humidity, suggesting that there was limited effect of soil carbon on the increased SWR when above the threshold soil water content since most organic carbon was removed from the wettable soil. We also investigated if there is any difference in the surface energy heterogeneity when exposed to 90% relative humidity to gain insight into surface chemistry heterogeneity of the soil particles' surfaces. Exposing soils to 90% relative humidity decreased the heterogeneity of the total and dispersive surface energy of both wettable and water‐repellent sandy soil indicating a more uniform surface chemistry than when exposed to 0% relative humidity. Highlights: Examined why soil water repellency (SWR) in a sandy soil increases at low soil water content. Explored underlying mechanisms via water adsorption isotherm and surface energy of a sandy soil. Increased SWR coincided with capillary water condensation and is likely due to counterion effects. Quantitative data presented new mechanisms on why SWR increases with increasing soil water content.